2023
DOI: 10.24996/ijs.2023.64.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Studying some cytotoxic and cytogenetic potentials of Dandelion methanolic extract on MCF-7 cancer cell line: an in vitro study

Abstract: This study aimed to evaluate the anticancer activity and cell division arresting by dandelion methanolic extract on breast cancer cell line MCF-7 cancer cell line. For achieving this goal, cytotoxicity assay (MTT assay), multipara system assay: High Content Screening (HCS) which include (viable cell count VCC; membrane permeability MP; cellular mitochondrial permeability CMP; nuclear intensity NI and cytochrome C releasing ), reactive oxygen species detection and cell cycle phases division were tested. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…There is need for precise diagnostic tools to guide treatment decisions [39]. Novel breast cancer treatment can help overcome resistance to therapy by inducing apoptosis in cancer cells [40,41] complexity of breast cancer [42,43]. Very recent studies have focused on the gene expression signature to sensitized breast cancer cells to particular chemotherapeutic agents such as Hesperetin [44].…”
Section: Discussionmentioning
confidence: 99%
“…There is need for precise diagnostic tools to guide treatment decisions [39]. Novel breast cancer treatment can help overcome resistance to therapy by inducing apoptosis in cancer cells [40,41] complexity of breast cancer [42,43]. Very recent studies have focused on the gene expression signature to sensitized breast cancer cells to particular chemotherapeutic agents such as Hesperetin [44].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Furthermore, several earlier investigations have demonstrated the anti-tumor potential of different dandelion extracts. [12][13][14][15] It has been reported in various studies that ethanol extract has a higher content of bioactive molecules than water extract. 16 Although the cytotoxicity of the water extract from the dried dandelion root on the pancreatic cancer cell line has already been established, 11 no research has been encountered in the literature about the cytotoxic impact of the ethanol extract made from the fresh dandelion root, which contains more bioactive molecules, on the PANC-1 cancer cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the effects of Mannich based on the growth of MCF-7 cells were found to inhibit cell growth in a dosedependent manner. Other research reported that Mannich bases could induce apoptosis in MCF-7 cells [7]. Another study investigated the effects of Mannich bases on the expression of genes involved in the growth and survival of MCF-7 cells.…”
Section: ■ Introductionmentioning
confidence: 99%